Intra-household exposure to labor market risk in the time of Covid-19: lessons from Mexico - Peluffo, Cecilia (2021)
The ability to work from home can be critical during pandemics. We calculate an index that measures the possibility of working from home based on the characteristics of the pre-Covid-19 pandemic distribution of occupations and on internet access at home, using microdata for Mexico. Focusing on households with two partners employed in nonessential occupations, we show that there is high within-household correlation in the possibility of working remotely, which is likely to be positively associated with job stability during the pandemic. Poor families, with low access to formal credit and who rely heavily on informal mechanisms for consumption smoothing have lower chances of working remotely than richer families with higher access to formal credit. High within-household correlation in the work-from-home index restricts the likelihood of intra-household risk-sharing and consumption smoothing, and is likely to contribute to an increase in inequality.